Development Of Schoology-Based E-Learning In Islamic Economics Course Tadris Study Program Kh Achmad Siddiq Institute Of Islamic Religion 2019 - Musyarofah Musyarofah; Moh Sutomo; Abdurrahman Ahmad (STAIFAS-Press, 2022)
Utilization of information technology has become a necessity in almost every sector of life, including the world of education by presenting e-learning systems in educational institutions to increase the effectiveness and flexibility of learning. E-learning enables learning interactions between students and educators by accessing information and subject matter/lectures anytime and anywhere . The same is true for learning the Islamic Economics course at the Social Sciences Tadris Study Program which in its implementation coincides with the Internship II activities at partner SMP/MTs, so that both activities can run well without having to leave one of them. The objectives of this study are: 1) To describe the development of Schoology - based E-learning in the Islamic Economics course at the Social Studies Tadris Study Program IAIN Jember in 2019 ?; 2). Describe the feasibility and effectiveness of Schoology - based E-learning development products in the Islamic Economics course at the Social Studies Tadris Study Program IAIN Jember in 2019 . This research uses an adapted research and development model from Sugiyono include : 1) Potential and problems; 2) Gathering information; 3) Product Design; 4) Design validation; 5) Design improvements; 6) Product trial: 7) Product revision; 8) Trial of use; 9) Product Revision; 10) Mass Product Manufacturing. The research instruments used were: 1) validation questionnaires for experts, 2) product applicability observation sheets, 3) practice questions, 4) assessment rubrics, 5) lecturer and student response questionnaires, and (5) interview guidelines for lecturers and students. The data obtained in the form of quantitative and qualitative. Quantitative data analysis used descriptive percentage technique . The results of the study show that: 1) E-learning products based on Schoology in the Islamic Economics course are arranged using features namely : Add file/Link/External Tools in the form of power point or Theory each chapter Islamic Economics , Add Discussion in the form of a discussion forum , Add Link in the form of connected learning videos with youtube , Add Test/ Quiz in the form of Quiz and Add Assignment in the form of Tasks , 2) The development of Schoology-based E-learning which is compiled has the feasibility of a material expert of 78.2%, which means that the Islamic Economics e-learning module material is valid or feasible to use. The results from IT experts and design percentages are 80% which means that the IT e-learning design is valid or feasible to use. The results of the assessment from the initial trial stage obtained an average percentage of 81.25%, which means that e-learning is very valid so that the product can be used without revision. Test the effectiveness of e-learning with use calculation NGain Score shows the average value of NGain Score is 0.5326 is categorized as moderate or quite effective, with a minimum N-Gain Score value of 0.14 and a maximum N-Gain Score value of 0.93. So it can be concluded that the use of e-learning schoolology in the Islamic Economics course is quite effective in improving the learning outcomes of Tadris IPS IAIN Jember students.